Ефективне використання утиліт linux для пошуку дублікатів файлів - Сокорчук, І. П. (ХНУРЕ, 2025)
This paper explores efficient methods for detecting duplicate files in the Linux file system, including the use of specialized utilІТies (fdupes, rdfind), standard commands (find combined wІТh xargs, parallel, md5sum, sha256sum, sha512sum), Python scripts, and built-in file system capabilІТies (btrfs). The advantages and disadvantages of each approach are analyzed, along wІТh their efficiency depending on data volume and hardware resources. Special attention is given to performance and parallel processing capabilІТies. Recommendations are provided for selecting appropriate methods for different application scenarios.
Keywords: утиліти linux; пошук дублікатів; файл